Relation Between Adhesion Properties and Microscopic Characterization of Polyphosphoric Acid Composite SBS Modified Asphalt Binder - Li, Liangying; Li, Zhiwei; Wang, Yongning; Li, Xiaolan; Li, Bo (Frontiers in Materials, 2021)
The purpose of the study is to investigate the adhesive properties of PPA/SBS modified asphalt, three base asphalt binders, one SBS, one dibutyl phthalate (DBP), one furfural extraction oil, and two polyphosphoric acid (PPA) are used to produce the modified binders. The tested adhesive properties in this study include contact angle, cohesive work, adhesive work and peak area ratio. cohesive work and adhesive work indicators are calculated from the contact angle, and the contact angle between polyphosphoric acid compounded SBS (PPA/SBS) modified asphalt and three liquids (distilled water, glycerin, formamide) was tested by contact angle tester，peak area ratio of microscopic adhesion performance index by AFM. The relationship between the microscopic adhesion performance characterization method (peak area ratio) and the macroscopic adhesion performance index (cohesive work, adhesion work) was established. The test results indicated that when under the conditions of 0.5%PPA,1%DBP,1.5%extracted oil, and 3.5%SBS, the PPA/SBS modified asphalt has the highest cohesive work and adhesion work, and is obviously beyond the original SBS modified asphalt, the peak area ratio is consistent with the cohesive work and adhesive work, and the correlation between peak area ratio and cohesive work and adhesion work is higher. The peak area ratio is recommended to adopt to characterize microscopic adhesion properties of PPA/SBS modified asphalt.